Compact energy dispersive X-ray microdiffractometer for diagnosis of neoplastic tissues. (August 2017) - Sosa, C.; Malezan, A.; Poletti, M.E.; Perez, R.D.
Abstract: An energy dispersive X-ray microdiffractometer with capillary optics has been developed for characterizing breast cancer. The employment of low divergence capillary optics helps to reduce the setup size to a few centimeters, while providing a lateral spatial resolution of 100 µm. The system angular calibration and momentum transfer resolution were assessed by a detailed study of a polycrystalline reference material. The performance of the system was tested by means of the analysis of tissue-equivalent samples previously characterized by conventional X-ray diffraction. In addition, a simplified correction model for an appropriate comparison of the diffraction spectra was developed and validated. Finally, the system was employed to evaluate normal and neoplastic human breast samples, in order to determine their X-ray scatter signatures. The initial results indicate that the use of this compact energy dispersive X-ray microdiffractometer combined with a simplified correction procedure is able to provide additional information to breast cancer diagnosis. Highlights: A compact μ -XRD spectrometer for biological tissue analysis has been developed. The system employs a capillary optics excitation and energy dispersive detector. The momentum transfer resolution is suitable for the tissue characterization. A simplified approach to correct the raw-acquired scattering profiles was proposed.